Analisis Biaya Produksi dalam Meningkatkan Penjualan - Irfan Faris Rudiana; Toto Toto; Dedi Rudiana (Universitas Indraprasta PGRI, 2021)
The company requires production costs in every run of its operational activities, production costs are used to process raw materials or semi-finished goods into finished products. The cost of raw materials, labor costs, and factory overhead costs become the main components in the formation of costs where these costs will determine the cost of production and the price of goods sold (HPP). Production costs are all costs associated with the goods produced, in which there is an element of raw material costs, labor costs, and factory overhead costs. The purpose of this study was to analyze: 1) Identification of the types of costs - costs in the business of lovebird cattle in Tasikmalaya. 2) determine the effect of production costs in increasing sales volume. The method used is a survey method with quantitative and qualitative approaches. The quantitative approach analyzes the effect of production costs on sales volume, while the qualitative approach to identify the types of costs used in lovebird livestock businesses in Tasikmalaya. The types of data collected are primary data and secondary data, with data collection techniques being documentation and interviews. While the technique of analysis with descriptive analysis. Based on the results of the simple regression t-test obtained a significance value of 0.055. Where 0.055 > 0.05 means that the production cost at each farm has an almost significant effect on the sales volume of lovebirds.